2021
DOI: 10.1080/0284186x.2021.1939146
|View full text |Cite
|
Sign up to set email alerts
|

Combination of aneuploidy and high S-phase fraction indicates increased risk of relapse in stage I endometrioid endometrial carcinoma

Abstract: Introduction: Endometrioid endometrial carcinoma is a cancer type with generally excellent prognosis when diagnosed at an early stage, but there is a subset of patients with relapsing disease in spite of early diagnosis and surgical treatment. There is a need to find prognostic markers to identify these patients with increased risk of relapse. Depth of myometrial invasion, histological grade, and presence of lymphovascular invasion are known risk factors. DNA content (ploidy) and proliferation measured as S-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It should be noted that we evaluated only two types of tumors in a different proportion than the study presented. An increased S‐phase fraction is associated with poorer prognosis in breast cancer 24 and in endometrioid endometrial carcinoma 25 when compared with cases with low rates. Although no long‐term follow‐up studies have been found investigating the prognostic value of S‐phase fraction and other cell cycle parameters in AM and AC, both neoplasms tend to progress aggressively, which may be an aneuploid feature of odontogenic tumors with a high S‐phase fraction.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that we evaluated only two types of tumors in a different proportion than the study presented. An increased S‐phase fraction is associated with poorer prognosis in breast cancer 24 and in endometrioid endometrial carcinoma 25 when compared with cases with low rates. Although no long‐term follow‐up studies have been found investigating the prognostic value of S‐phase fraction and other cell cycle parameters in AM and AC, both neoplasms tend to progress aggressively, which may be an aneuploid feature of odontogenic tumors with a high S‐phase fraction.…”
Section: Discussionmentioning
confidence: 99%